Strengthening MSMEs in Aan Tourism Village through a Green Supply Chain Management Scorecard Approach Based on the Local Wisdom of Tri Hita Karana - Made Irma Dwiputranti; I Gusti Agung Prabandari Tri Putri; Ida Bagus Ardi Putra; D. A. Gladysia Sistadanta Kurnia Dewi Sutedja; Maria Gratiani Hardi Saputri; Muntoha Surya Nugroho (International Journal of Management Science and Information Technology, 2026)
Tourism development in Bali contributes significantly to regional economic growth, yet it also creates environmental and social challenges, particularly in tourism villages. This study analyzes sustainability practices in Aan Tourism Village from environmental, social, and economic perspectives, measures readiness for Green Supply Chain Management (GSCM) implementation, and formulates a conceptual model to support sustainable tourism development. A qualitative case study approach was employed, with data collected through field observations, in-depth interviews, focus group discussions, and document analysis. Readiness was assessed using a GSCM Scorecard consisting of six dimensions: internal management, green design, green purchasing, green production, green logistics, and reverse logistics. The findings show that Aan Tourism Village achieved an average score of 4.3, categorized as Green, indicating that most tourism activities have implemented GSCM practices consistently. Internal management and reverse logistics achieved the Very Green category, while green purchasing and green logistics require further improvement. The study proposes an input-process-output-outcome-based GSCM model that is adaptive to local conditions and can serve as a strategic reference for sustainable tourism village development. Practically, these findings offer village administrator a replicable scorecard instrument for periodic sustainability audits, and provide policymaker with evidence-based priorities for green infrastructure investmen in rural tourism context.